Prescriptive-Based Building Regulations: Challenges and Recommendations for Modernization in the Case of Bangkok - Mannontaratana, Pornprom; Laovisutthichai, Vikrom; Viryasiri, Traiwat; Jamnothai, Monsicha; Poonpermpun, Watinee (Nakhara : Journal of Environmental Design and Planning, 2025)
Prescriptive building codes have long structured urban development by offering rule-based standards that ensure safety, uniformity, and ease of enforcement. Despite widespread reliance on prescriptive codes in developing countries, there is limited empirical evidence guiding their modernization or hybridization. This research investigates the challenges of prescriptive-based building regulations in the context of Bangkok, Thailand, and explores pathways toward more effective and modernized regulatory frameworks. Through regulatory review, focus groups, and public discussions with professionals, government officials, and private sectors, the study identifies four core problems: complexity, inconsistency, redundancy, and obsolescence. It then proposes a hybrid approach that improves existing prescriptive systems while integrating performance-based elements to enhance regulatory flexibility, clarity, and efficiency. Key recommendations include simplifying legal structures, ensuring regular updates, resolving overlapping provisions, and introducing visual legal tools and digital platforms. The findings contribute to both academic and practical discussions, serving as a foundational reference for regulatory reform, particularly in developing urban contexts where institutional capacities and resources may vary. Future studies are recommended to test proposed reforms empirically and explore their applicability in diverse legal and administrative settings.